Zat Pengatur Tumbuh dalam Nutrisi Hidroponik pada Pertumbuhan dan Hasil Tanaman Pakchoy (Brassica rapa). - Surtinah Surtinah; Seprita Lidar (Politeknik Negeri Lampung., 2017)
This research were conducted using the plant growth regulator treatment plan consists of three threatments (without ZPT, ZPT superior plant growth (hantu), and ZPT gibgrow). Environmental design used was a complete randomized design with six replications. Data were analyzed using analysis of variance and multiple range test DMRT level of 5%. The results obtained are given ZPT hydroponic growing media to improve the growth and yield pakcoy, and ZPT hantu is best to plant growth substances.